2021
DOI: 10.31497/zrzyxb.20210515
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern evolution and convergence of water eco-civilization development index in China

Abstract: Spatial correlation and convergence of the development level of China's water ecocivilization is vital to its coordinated construction. Constructing an evaluation system of water eco-civilization construction, whose dimensions contain water security, water ecology, water environment, water conservation, water supervision and water culture, this paper adopts entropy methods to measure water eco-civilization development index of China and its 31 provincial-level regions from 2010 to 2018, uses exploratory spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…With the reduction of the marginal effect of the above-mentioned policies and a series of documents related to the pilot construction of WEC, the WEC growth rate fell back in 2017 and 2018 but then gradually increased to the maximum level due to the implementation of environmental protection policies and regulations, such as the Environmental Protection Tax Law, the Reform Program of the Ecological and Environmental Damage Compensation System, and the newly revised Water Pollution Prevention and Control Law. From the perspective of space, the average annual growth rate of WEC in the upper, middle, and lower reaches of the YREB is 0.148, 0.111, and 0.261, respectively, presenting the completely opposite situation to that of NU, with the trend of decreasing successively in the lower reaches, upper reaches, and middle reaches, which is consistent with the research conducted by Yu et al and Su et al [12,68]. This is mainly because the lower reaches of the YREB, which have a strong economic foundation and strong investment in infrastructure, have laid a good foundation for environmental protection and sewage treatment.…”
Section: Evaluation Resultssupporting
confidence: 90%
“…With the reduction of the marginal effect of the above-mentioned policies and a series of documents related to the pilot construction of WEC, the WEC growth rate fell back in 2017 and 2018 but then gradually increased to the maximum level due to the implementation of environmental protection policies and regulations, such as the Environmental Protection Tax Law, the Reform Program of the Ecological and Environmental Damage Compensation System, and the newly revised Water Pollution Prevention and Control Law. From the perspective of space, the average annual growth rate of WEC in the upper, middle, and lower reaches of the YREB is 0.148, 0.111, and 0.261, respectively, presenting the completely opposite situation to that of NU, with the trend of decreasing successively in the lower reaches, upper reaches, and middle reaches, which is consistent with the research conducted by Yu et al and Su et al [12,68]. This is mainly because the lower reaches of the YREB, which have a strong economic foundation and strong investment in infrastructure, have laid a good foundation for environmental protection and sewage treatment.…”
Section: Evaluation Resultssupporting
confidence: 90%
“…The extant literature found that the level of Jiangxi's WEC shows a fluctuating upward trend and significant urban differences. This result is also similar to the findings of Deng et al and Su et al on the level of WEC in China [13,48]. They found that the level of WEC in China continues to rise, with significant differences between different provinces, indicating that the application of the PSR model to construct the indicator system of WEC is reasonable and has a particular reference value.…”
Section: Discussionsupporting
confidence: 90%
“…The result confirmed that the uneven spatial distribution of water resources affects the water ecological environment and water ecological civilization. Moreover, this result is similar to the studies by Deng et al and Su et al on the development level of China's water ecological civilization [42,43]. The former found that the level of China's water ecological civilization construction continued to improve from 2010 to 2016, and the gap of the level of 31 provinces is significant and not narrowing.…”
Section: Discussionsupporting
confidence: 90%